Impact of Asha Intervention on Stigma among Rural Indian Women with AIDS - Nyamathi, Adeline (2013)
Rural women living with HIV/AIDS (WLA) in India face multifarious challenges which affect access to antiretroviral regimens and management of HIV/AIDS. The purpose of this pilot study, using cluster randomization, is to compare the effectiveness of the Asha-Life (AL) intervention, delivered by HIV-trained village woman, Asha (Accredited Social Health Activist), with a Usual Care (UC) group on reduction of internalized stigma and avoidant coping among 68 women living with AIDS (WLA) in rural India over a six-month period. The findings demonstrated that participation in the AL intervention was associated with significant reductions in internalized stigma and the use of avoidant coping strategies at follow-up. The findings of our study are promising in terms of the role rural village women (Asha) may play in reducing internalized stigma and avoidant coping in the lives of rural women living with AIDS in India.